Parental Involvement in Music Education - Cikač, Naja (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter discusses the importance of parental involvement in music education and the various roles parents play in supporting music learning. Parents, drawing on their knowledge of their child, can contribute to their child's musical progress in several ways: as supervisors at home, assisting with tasks; as supporters, providing financial and emotional encouragement; and as role models, fostering perseverance and motivation through positive examples. Research (Dell et al., 2014; Knott, 2018; Ang et al., 2020; Zdzinski, 2013; Brand, 1986) indicates that children's musical achievement improves when they grow up in a stimulating musical environment with active parental support, as this enhances their motivation. Parental involvement is crucial for long-term success in music education, while simultaneously supporting the child's autonomy.